New Econometric Model of Sustainable Economic Development Quantifying the Impact of The Implementation of SDG9 in the European Context - Costinela Fortea; Valentin Marian Antohi; Monica Laura Zlati; Sajjad Nawaz Khan (Revista de Studii Financiare)
In the context of European integration, sustainable economic development in the European Union is a strategic priority. In recent years, the European Union has made progress towards sustainable development objectives, reflecting a commitment to economic growth that respects the principles of environmental protection, social equity and economic efficiency. The European Union plays an important role in shaping sustainable development policies and initiatives through legislation, directives and financial funds aimed at both protecting the environment and stimulating innovation and competitiveness. We aim to analyse the level of innovative sustainability of the European economy in relation to the European dimension of innovative sustainability using an econometric model. The methods used consist of a literature survey, database consolidation and econometric modelling. The econometric model shows that environmental taxes and raw material consumption have a negative impact on GDP per capita in the short run, while technological innovation, measured by the number of patents and R&D personnel, contributes significantly to economic growth and sustainable development, underlining the need for long-term investment in human capital and green technologies to support the competitiveness and sustainability of European economies. The results of the study will lead to the formulation of European public policies on sustainable economic development regarding the implementation of Sustainable Development Goal 9.